Laser Polishing of Additive Manufactured Aluminium Parts by Modulated Laser Power - Markus Hofele (MDPI AG, 2021)
In this study a new approach to laser polishing with periodic modulated laser power in the kilohertz regime is introduced. By varying the modulation frequency and modulation time, different periodic laser power curves with varying minimum, peak and average laser power can be created. The feasibility of the method is shown by polishing of vertical built AlSi10Mg L-PBF parts with an initial roughness of Ra = 12.22 µm. One polishing pass revealed a decreasing surface roughness with increasing energy density on the surface up to Ra = 0.145 µm. An increasing energy density results in a rising remelting depth between 50 and 255 µm and a rising relative porosity of 0.3% to 4.6%. Furthermore, the thermal process stability, analysed by the melt pool length in scanning direction, reveals a steadily increasing melt pool dimension due to component heating. Multiple laser polishing passes offers a further reduced surface roughness, especially at higher modulation frequencies and provides an improved orientation independent roughness homogeneity. The process stability regarding varying initial surface roughness revealed an almost constant relative roughness reduction rate with an achievable roughness variation after two polishing passes between Ra = 0.13–0.26 µm from an initial state of Ra = 8.0–19.2 µm.